Phylogenetic evidence for a shift in the mode of mammalian body size evolution at the Cretaceous‐Palaeogene boundary. Issue 8 (9th August 2013) - Slater, Graham J.
Summary: Phylogenetic comparative methods provide a powerful way of addressing classic questions about tempo and mode of phenotypic evolution in the fossil record, such as whether mammals increased in body size diversity after the Cretaceous‐Palaeogene (K‐Pg) extinction. Most often, these kinds of questions are addressed in the context of variation in evolutionary rates. Shifts in the mode of phenotypic evolution provide an alternative and, in some cases, more realistic explanation for patterns of trait diversity in the fossil record, but these kinds of processes are rarely tested for. In this study, I use a time‐calibrated phylogeny of living and fossil Mammaliaformes as a framework to test novel models of body size evolution derived from palaeontological theory. Specifically, I ask whether the K‐Pg extinction resulted in a change in rates of body size evolution or release from a constrained adaptive zone. I found that a model comprising an Ornstein–Uhlenbeck process until the K‐Pg event and a Brownian motion process from the Cenozoic onwards was the best supported model for these data. Surprisingly, results indicate a lower absolute rate of body size evolution during the Cenozoic than during the Mesozoic. This is explained by release from a stationary OU process that constrained realized disparity. Despite a lower absolute rate, body size disparity has in fact been increasing since the K‐Pg event. The use of time‐calibrated phylogenies of living and extinct taxa and realistic, process‐based models provides unparalleled power in testing evolutionary hypotheses. However, researchers should take care to ensure that the models they use are appropriate to the question being tested and that the parameters estimated are interpreted in the context of the best fitting model.